2017
DOI: 10.5539/jmbr.v7n1p186
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA gyrase Subunit a Mutations Associated with Ciprofloxacin Resistance in Staphylococcus aureus Isolated from Nasal Infection in Kurdistan-Iran

Abstract: Fluoroquinolone antibiotics such as ciprofloxacin are useful drugs against infections caused by Staphylococcus aureus and mutations in DNA gyrase which control bacterial DNA topology, can be one of the reason of occurrence resistance to this class of antibiotics. Therefore finding new mutations and study of the quinolone interaction with mutated GyrA can provide important issues for explanation resistance. In this study 5 ciprofloxacin resistance Staphylococcus aureus isolated among 50 collected S.aureus strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
2
6
0
Order By: Relevance
“…The detection of both plasmid mediated quinolone resistance (PMQR) genes (qnrB, qnrS and aac(6')-Ib-cr) and chromosomal mediated quinolone resistance (CMQR) genes (gyrA, gyrB, and parC) in the ciprofloxacin-resistant S. aureus isolates is an indication that these genes may be responsible for the observed resistance to ciprofloxacin. The detection of gyrA, gyrB and parC agrees with reports [14,27,43]. The occurrence rates of gyrA, and gyrB were similar and higher than that of parC [43] but not so as reported by [44].…”
Section: Molecular Detection Of Quinolone Resistance Genessupporting
confidence: 89%
See 3 more Smart Citations
“…The detection of both plasmid mediated quinolone resistance (PMQR) genes (qnrB, qnrS and aac(6')-Ib-cr) and chromosomal mediated quinolone resistance (CMQR) genes (gyrA, gyrB, and parC) in the ciprofloxacin-resistant S. aureus isolates is an indication that these genes may be responsible for the observed resistance to ciprofloxacin. The detection of gyrA, gyrB and parC agrees with reports [14,27,43]. The occurrence rates of gyrA, and gyrB were similar and higher than that of parC [43] but not so as reported by [44].…”
Section: Molecular Detection Of Quinolone Resistance Genessupporting
confidence: 89%
“…And only a few resistances were observed in the fluoroquinolones (ciprofloxacin and levofloxacin) 19.6% and 5.9% respectively in the test. This observation is similar to that of 10% ciprofloxacin S. aureus resistance reported [14] from clinical isolate from nasal infection in Kurdistan-Iran, 9% ciprofloxacin as reported [22] in public hospitals in Ghana and 6.0% levofloxacin resistance as reported [10], generally indicating low resistance to the fluoroquinolone antibiotics. This suggest that these fluoroquinolone antibiotics may not have been misused indiscriminately or abused in those study locations, and thus remains a good drug of choice for the treatment of infections caused by S. aureus.…”
Section: Molecular Detection Of Quinolone Resistance Genessupporting
confidence: 84%
See 2 more Smart Citations
“…The sequences of the PCR product was obtained and compared to sequences of gyrA and parC genes from NCBI, the results shown that 40 and 51 mutations in the forward and reverse strands, respectively, were detected in gyrA of the tested isolate; since gyrA encode for DNA gyrase. Such mutations would lead to amino acid substitutions, alter the target protein for fluoroquinolone structure and subsequently the fluoroquinolone binding affinity of the enzyme, leading to drug resistance [23]. On the other hand; after comparing the obtained sequence of parC from the tested isolate with sequences from NCBI, the result revealed complete similarity and no mutations were recorded.…”
Section: Detection Of Meca Gene In S Aureus Isolatesmentioning
confidence: 99%